EFEKTIVITAS PELAKSANAAN AMDAL DALAM PENCEGAHAN KERUSAKAN LINGKUNGAN HIDUP AKIBAT KEGIATAN PERINDUSTRIAN DI INDONESIA - Pelangi Asy-Syifaa; Abdurrozzaq Hasibuan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The implementation of preventing environmental damage due to industrial activities in Indonesia, AMDAL is a very important document to be prepared. AMDAL contains instruments to prevent environmental damage and prevent environmental pollution (Law No. 32 Year 2009). The development process and the implementation of EIA must really pay attention to environmental sustainability, so as not to cause great harm to current and future generations. This research aims to gather sufficient information on the effectiveness of AMDAL implementation in preventing environmental damage due to industrial activities in Indonesia. This research uses the literature study method by collecting several previous studies to answer the effectiveness of EIA implementation in preventing environmental damage due to industrial activities in Indonesia. The results of this study indicate that the effectiveness of the implementation of EIA activities is very important and must be implemented by all business actors, companies or industries in order to prevent environmental damage and pollution around these business activities, companies or industries